Metal Oxide (MO) Surge Arresters - Stresses and Test procedures - Richter, Bernhard (2013)
The WG A3.17 of SC A3 took on the task of evaluating the stresses on MO arresters and reviewing the existing test procedures. Further on, the actual state of MO arrester design was investigated, as well as various applications in different types of electrical networks. Emphasis was given to the MO resistors as the active part of the MO arresters. A research project was started to experimentally investigate the energy handling capability of the MO resistors. The resulting TB covers and describes the actual MO resistor and arrester technology and the results of the first part of the research project.